2023
DOI: 10.1007/s10802-023-01111-7
|View full text |Cite
|
Sign up to set email alerts
|

Dimensions of Warm Parenting Attributions Differentiate Conduct Problem Subtypes in Young Children

Abstract: Understanding the developmental psychopathology of child conduct problems (CP) has been advanced by differentiating subtypes based on levels of internalizing problems (INT) and/or callous-unemotional (CU) traits (i.e., low empathy/guilt, poor motivation, shallow/deficient affect). The current study sought to elucidate prior inconsistencies in the role of warm/positive and harsh/negative parenting subcomponents in CP by differentiating subtypes on the basis of INT and CU traits. Parents of 135 young children (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…This profile involves co-occurring externalizing problems, internalizing problems, and CU traits, occurring in the presence of adverse childhood experiences, and often includes peripheral symptoms of ADHD/impulsivity, PTSD, and/or borderline personality disorder (BPD) (Cecil et al, 2018;Kahn et al, 2013;Kimonis et al, 2012b;Lee et al, 2010;Vaughn et al, 2009). With evidence for the existence of primary and secondary CU variants from early childhood (age 3: Ezpeleta et al, 2017;Fanti & Kimonis, 2017;Kaouar et al, 2023), this model is heavily informed by developmental psychology, developmental psychopathology, child clinical psychology, and health psychology (i.e., focused on the effects of toxic stress on the developing child) literatures. The proposed developmental mechanisms are intended to be distinct from both primary CU variants and conduct problems presenting in the absence of CU traits (hereafter referred to as "CP-only").…”
Section: A Revisited Theoretical Model For the Development Of Seconda...mentioning
confidence: 99%
See 2 more Smart Citations
“…This profile involves co-occurring externalizing problems, internalizing problems, and CU traits, occurring in the presence of adverse childhood experiences, and often includes peripheral symptoms of ADHD/impulsivity, PTSD, and/or borderline personality disorder (BPD) (Cecil et al, 2018;Kahn et al, 2013;Kimonis et al, 2012b;Lee et al, 2010;Vaughn et al, 2009). With evidence for the existence of primary and secondary CU variants from early childhood (age 3: Ezpeleta et al, 2017;Fanti & Kimonis, 2017;Kaouar et al, 2023), this model is heavily informed by developmental psychology, developmental psychopathology, child clinical psychology, and health psychology (i.e., focused on the effects of toxic stress on the developing child) literatures. The proposed developmental mechanisms are intended to be distinct from both primary CU variants and conduct problems presenting in the absence of CU traits (hereafter referred to as "CP-only").…”
Section: A Revisited Theoretical Model For the Development Of Seconda...mentioning
confidence: 99%
“…There is robust evidence that secondary CU variants experience extreme levels of adverse childhood experiences and particularly dysfunctional parenting (Craig et al, 2021a). The nature of their adversity is broad, ranging from low maternal warmth/sensitivity (Craig et al, 2021a;Fanti & Kimonis, 2017;Kaouar et al, 2023) and affectionless and rejecting parenting (Karpman, 1941), to parenting that is harsh (Goulter et al, 2017;cf. Bégin et al, 2021;Craig et al, 2021a;Humayun et al, 2014), hostile and verbally aggressive (Craig et al, 2021a), to childhood maltreatment (i.e., sexual or physical abuse or neglect; Bégin et al, 2021;Goulter et al, 2019;Kahn et al, 2013;Kimonis et al, 2011Kimonis et al, , 2012aKimonis et al, , 2017aKimonis et al, , 2017bPorter, 1996), to experiencing interpersonal traumatic events including witnessing intimate partner violence and other violence exposure (Bennett & Kerig, 2014;Docherty et al, 2016;Kahn et al, 2013;Sharf et al, 2014;Tatar et al, 2012), to broader cumulative environmental risk across early childhood (Cecil et al, 2014).…”
Section: Extreme Adverse Parenting Experiencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the primary variant of CU is theorized to be characterized by low anxiety and arise from more heritable risk, whereas the secondary variant is characterized by high anxiety and maltreatment experiences [ 1 , 6 , 7 ]. Some initial evidence has even suggested that these two variants can be observed in children as young as three [ 8 , 9 , 10 ]. Given potential differences in etiologies and responsivities to treatment programs between the two variants [ 11 ], it is important to further understand the distinction between the two variants, as such knowledge may inform psychological assessments and interventions by helping in tailoring the approaches to therapy and support.…”
Section: Introductionmentioning
confidence: 99%